2002
DOI: 10.1359/jbmr.2002.17.5.879
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Analogue-Specific Recruitment of Vitamin D Receptor Coactivators

Abstract: Synthetic ligands for the vitamin D receptor (VDR) are potential therapeutic agents for metabolic, neoplastic, and autoimmune disorders. Some of these ligands have similar or more potent antiproliferative, yet reduced hypercalcemic actions, than calcitriol. However, the mechanisms for these differential actions have not been clearly defined. We hypothesized that these gene-and tissue-specific effects may relate to ligand-directed selective recruitment of transcriptional coactivators. To identify key elements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…These findings led to the hypothesis that the specific profile of these analogs might be explained at the next level of transcriptional regulation by 1,25-(OH) 2 D 3 : the recruitment of coactivator molecules. Recent studies describe the effect of different analogs of 1,25-(OH) 2 D 3 on the interaction of VDR with coactivators (Takeyama et al, 1999;Issa et al, 2002). The present study investigates the 14-epi-analogs TX522 and TX527 and their influence on VDR-mediated recruitment of the coactivators TIF2, SRC-1, and DRIP205.…”
Section: Discussionmentioning
confidence: 95%
“…These findings led to the hypothesis that the specific profile of these analogs might be explained at the next level of transcriptional regulation by 1,25-(OH) 2 D 3 : the recruitment of coactivator molecules. Recent studies describe the effect of different analogs of 1,25-(OH) 2 D 3 on the interaction of VDR with coactivators (Takeyama et al, 1999;Issa et al, 2002). The present study investigates the 14-epi-analogs TX522 and TX527 and their influence on VDR-mediated recruitment of the coactivators TIF2, SRC-1, and DRIP205.…”
Section: Discussionmentioning
confidence: 95%
“…This may prolong the half-life of the activated receptor, affect the DNA binding properties or promoter selectivity of the activated VDR and influence receptor interactions with tissue-specific co-factors. These factors determine the tissue-selectivity of vitamin D metabolites and may also explain how different vitamin D metabolites can induce differential gene expression profiles in the same cell [57,58].…”
Section: The Molecular Basis For Differential Actions Of Vitamin D Mementioning
confidence: 99%
“…These differences could be multifactorial, e.g., different affinity to VDR (113), different magnitude of the transactivation of several genes (15), secondary to differences in the conformational changes and corepressors or coactivators recruitment. In fact, it has been demonstrated that VDR bound to paricalcitol or 22-oxacalcitriol recruits different coactivators from those recruited by the same receptor when bound to calcitriol (51,117).…”
Section: Present Use Of Vdras In Patients With Ckdmentioning
confidence: 99%